18 Intermittent hypoxia improves atherosclerosis associated with upregulation of hif-1α and nf-κb in aortic arch and serum of rabbits. (5th December 2017) - Pang, JX; Wang, BJ; Li, YC; Zhang, H; Xiang, WP; Hao, XW; Xue, H
Abstract : Objectives: To investigate the role of HIF-1α and NF-κB in intermittent hypoxia (IH) induced atherosclerosis in rabbits. Methods: New-Zealand White rabbits were exposed to IH for 12 weeks (intermittent hypoxia of 21% O2 for 30 s and 8% O2 for 30 s, cyclically repeated for 8 h/day). We randomly assigned 48 male rabbits to groups of normoxia (RA) or IH. The rabbits in the RA group were continuously exposed to room air. After intervention of 4, 8, and 12 weeks, serum and aortic arch tissues were subjected to Elisa and immunohistochemical staining analyses respectively. The formation of atherosclerosis in the aortic arch was observed by HE. Results: The formation of atherosclerosis in aortic tissue was observed by HE staining after IH. Compared with the RA rats, the level of HIF-1α and NF-κB in the serum of IH rats started to increase 4, 8, and 12 weeks after the beginning of the experiment (p<0.05). The level of HIF-1α in IH rats was highest at 4 w, and there was no change between 8 w and 12 w (p>0.05). NF-κB protein expression was significantly increased after IH (p<0.05). HIF-1α and NF-κB positive cells in aortic tissue from IH rabbits were induced to a much higher level compared with normal controls (p<0.05). Compared with IH rabbits after 4 w, the positive cells of HIF-1α and NF-κB were higher at 8 w and 12 w after IH (p<0.05). Conclusions: IH may, through increased HIF-1α and NF-κB in rabbits, lead to lipid deposition, which leads to the formation of atherosclerosis and the occurrence of cardiovascular and cerebrovascular diseases.